Running as a Middle - Class Sport: A Case Study of Mari Lari Film in Indonesian Movies - Meistra Budiasa (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
Sport is portrayed as an entertaining activity that various people from different social class like. Any information from sports can be seen through media. Therefore, sports and media are correlated because in general the role of the media is to attract public attention. Other than that, sports have various concepts that can be interpreted symbolically, one of which is by social groups through the mediazitaion. This research uses Critical Discourse Analysis (CDA) to examine how Mari Lari can represent the sosial class lifestyle. The results show how the middle class is represented through visual cues such as clothing styles, and choice of sports. In addition, this research is expected to be a reference for further researchers who want to review films about sports.